ANALISIS TIME VALUE OF MONEY ATAS PROSES PENYELESAIAN RESTITUSI PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. KRAKATAU DAYA LISTRIK TAHUN 2018 - Muyasaroh Muyasaroh (Universitas Gajayana Malang, 2018)
Value Added Tax refund is one of the rights of taxpayers to ask for the overpayment of tax result principle of tax credit methods. This research aims to determine the completion of the refunds process that was associated with the time value of money from the refunds and a case study on PT. Krakatau Daya Listrik in 2018. The formulation of the problem in this study are (1) How is the process of completing Value Added Tax (VAT) restitution at PT. Krakatau Daya Listrik ? (2) What is the process of completing VAT refunds if it is associated with Time Value of Money at PT. Krakatau Daya Listrik ? The research is a descriptive method with qualitative approach through the techniques of data collection such as interviews, observation and documentation. The data sources used are primary and secondary data, namely SPT Period VAT, SPHP (Notification of Results of Examination), SKPLB (Overpayment Tax Assessment Letter), SPMKP (Warrant Paying Excess Tax) PT. Krakatau Daya Listrik 2018. The results of this study explained that the process of returning restitution which has a span of 12 months since the application was received in full with the results received in the amount of Rp 6,942,060,577 will have a bearing on the time value of money from the restitution money received by PT. Krakatau Daya Listrik. Assuming the calculation of the time value of money invested in deposits on the results of VAT refunds has a difference in the value of money in the amount of Rp. 926,881,713.65 with a percentage of 13.35% for calculations using the future value formula and the difference in the reduction in the value of money in the amount of Rp. 817,704,434.24 with a percentage of 11.77% for calculations using the present value formula in 2020.